2013
DOI: 10.1177/0959683613508156
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Holocene sea-level and coral reef demise: U-Th dating of subfossil corals in Moreton Bay, Australia

Abstract: It is increasingly apparent that sea-level data (e.g. microfossil transfer functions, dated coral microatolls and direct observations from satellite and tidal gauges) vary temporally and spatially at regional to local scales, thus limiting our ability to model future sea-level rise for many regions. Understanding sealevel response at 'far-field' locations at regional scales is fundamental for formulating more relevant sea-level rise susceptibility models within these regions under future global change projecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 111 publications
(180 reference statements)
1
16
0
Order By: Relevance
“…Corals currently grow primarily around islands in the southern part of the bay, but true reef development to sea level is absent (Lybolt et al, 2011). However, Holocene reef growth was much more widespread and major fringing reefs occupied the western shores of the bay between Wellington Point and Cleveland (Leonard et al, 2013). The locations of corals used in this study are shown in Fig.…”
Section: Study Sites and Modern Ocean Circulation In Sw Pacificmentioning
confidence: 99%
See 1 more Smart Citation
“…Corals currently grow primarily around islands in the southern part of the bay, but true reef development to sea level is absent (Lybolt et al, 2011). However, Holocene reef growth was much more widespread and major fringing reefs occupied the western shores of the bay between Wellington Point and Cleveland (Leonard et al, 2013). The locations of corals used in this study are shown in Fig.…”
Section: Study Sites and Modern Ocean Circulation In Sw Pacificmentioning
confidence: 99%
“…2. They were recovered from various points along the western margin of the bay from Wellington Point to Cleveland and from Peel, Goat, Coochiemudlo, and Macleay islands, which extend the distribution across the bay (Lybolt et al, 2011;Leonard et al, 2013). Griffin (1993, 1999) measured 14 C content in biannual coral samples from Heron Island (23 • S, 152 • E) and Abraham Reef (22 • 06 S, 153 • 00 E) in the southern GBR.…”
Section: Study Sites and Modern Ocean Circulation In Sw Pacificmentioning
confidence: 99%
“…UeTh dating (also known as U-series dating or 238 Ue 234 Ue 230 Th disequilibrium dating) is an isotopic dating technique commonly used to determine the age of carbonate materials, such as speleothem and coral (Price et al, 2009a;Yu et al, 2012;Leonard et al, 2013). The dating method is based on the decay of 238 U to stable 206 Pb via intermediate daughter isotopes, such as 234 U (with a half-life of 245,250 ± 490 years, see Cheng et al, 2000) and 230 Th (with a half-life of 75,690 ± 230 years).…”
Section: Ueth Datingmentioning
confidence: 99%
“…The large barrier islands of Moreton Bay are sand islands, formed as a result of sand mobilisation and accretion as sea-level rose and fell throughout the Pleistocene (Leonard et al, 2013). Peel Island, however, is a rocky land mass, and would have been a high point on the Moreton plain at times of low sea-level, just as it is a prominent island at times of high sea-level.…”
Section: The Peel Island Lazaret Middenmentioning
confidence: 98%